ANALISIS HUBUNGAN ANTARA FAKTOR SOSIAL EKONOMI DAN TINGKAT KEDINAMISAN ANGGOTA KELOMPOK TANI - Paulus A. Sole; Mustafa Abdurrahman; Serman Nikolaus (Undana Press, 2020)
This research aimed to assess dynamics level of the members of the Harapan Makmur farmers' group in the village of Tuatuka, East Kupang District, Kupang Regency and the relationship between socio-economic factors (age, formal education, non-formal education, number of family- dependent people, income, agricultural experience) with the dynamics level of farmer group members of Harapan Makmur Tuatuka Sub-District, East Kupang District, Kupang Regency. This research used the case study method. The sample used is all farmers who are members of prosperous farmer groups of 35 respondents. Analysis of the data used in this research used a Likert scale and the Sperman rank correlation test (rs). The results showed that the age of majority respondents was classified as productive (85.70%), formal education was classified as low (60.00%), non-formal education was classified as high (91.43%), the number of dependent persons was quite high (62.86)%), long experience in agriculture (37.14%) and agricultural income wass quite high (88.58%). The dynamic level of the members of Harapan Makmur farmer group in Tuatuka subdistrict, East Kupang district, Kupang Regency was in the dynamic category (68.0%). ), The results of the analysis (rs) showed that socio- economic factors (age, formal education, non-formal education, number of family members, income,agricultural experience) that were related to the dynamics of the farmer group members were non- formal education. While other socio-economic factors had no real connection with the dynamics of Harapan Makmur farmer group in the village of Tuatuka, East Kupang District, Kupang Regency.